Occurrence of Listeria monocytogenes in irrigation water and irrigated vegetables in selected areas of Osun State, Nigeria - Temitope Deborah Agboola; Mary Adejumoke Bisi-Johnson (Scientific African, 2023)
Listeria monocytogenes is a known pathogen that had been reported to be significant in biomedical field due to the role it played in both food and medical microbiology. This study examined the incidence of L. monocytogenes in selected irrigation water and irrigated vegetables in Osun State with a view to providing information on the seasonal distribution of the bacteria strain in the study area their virulence as well as genetic relatedness. A total of 72 irrigation water samples, 48 Amaranthus spp and 24 Lycopersicon spp samples were collected in the morning, twice raining and dry seasons between 2019 and 2020 from the East, West and Central senatorial districts of Osun State, Nigeria. Listeria monocytogenes were isolated using PALCAM Agar (selective medium) after enrichment with frazer broth and confirmed using Polymerase Chain Reaction (PCR) with genes that codes for genus Listeria (Prs) and virulence in L. monocytogenes (Hly A, Clp E, Plc A, Plc B, prf A and Inl B genes). Listeria monocytogenes (n = 24) were confirmed by PCR and statistically, the distribution of the organisms across sampling sites showed no significant difference (p-value = 0.2282) with respect to season. All the isolates were positive for Prs, Hly A and prf A which codes for the genus Listeria, listeriolysin and virulence regulator respectively. Only four (4) and six (6) L. monocytogenes were positive for inl B (562 bp) and clp E (518 bp) genes respectively. There is genetic relationship between isolates obtained from water and Lycopersicon sp obtained from Osun Central and West with one isolate obtained from Amaranthus sp from Osun East in cluster 4. The study concluded that irrigation water play a role in dissemination of Listeria monocytogenes in the sampled vegetables in this environment and therefore constitute potential risk of food safety if the vegetables are consumed without proper processing.